War - Woodward, Bob, 1943- (Simon & Schuster, 2024)
"War is an intimate and sweeping account of one of the most tumultuous periods in presidential politics and American history. We see President Joe Biden and his top advisers in tense conversations with Russian president Vladimir Putin, Israeli prime minister Benjamin Netanyahu and Ukrainian president Volodymyr Zelensky. We also see Donald Trump, conducting a shadow presidency and seeking to regain political power. With unrivaled, inside-the-room reporting, Woodward shows President Biden's approach to managing the war in Ukraine, the most significant land war in Europe since World War II, and his tortured path to contain the bloody Middle East conflict between Israel and the terrorist group Hamas. Woodward reveals the extraordinary complexity and consequence of wartime back-channel diplomacy and decision-making to deter the use of nuclear weapons and a rapid slide into World War III. The raw cage-fight of politics accelerates as Americans prepare to vote in 2024, starting between President Biden and Trump, and ending with the unexpected elevation of Vice President Kamala Harris as the Democratic nominee for president. War provides an unvarnished examination of the vice president as she tries to embrace the Biden legacy and policies while beginning to chart a path of her own as a presidential candidate."--